THE EFFECT OF A SLOW RELEASE IMPLANT CONTAINING THE GnRH AGONIST DESLORELIN ON PITUITARY AND TESTICULAR FUNCTION IN MATURE MALE DOGS - Junaidi .; P.Williamson .; J.M. Cummins .; G.B. Martin .; T. Trigg . (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2000)
.